1990
DOI: 10.1152/jappl.1990.69.1.232
|View full text |Cite
|
Sign up to set email alerts
|

Functional and morphological changes in the eccrine sweat gland with heat acclimation

Abstract: Three adult male patas monkeys (11-15 kg) were heat acclimated by continuous exposure to an ambient temperature of 33 +/- 1 degree C at 13% relative humidity for 9 mo. During the last month, they were also exposed to 45 degrees C at 10% relative humidity for 4 h/day and 5 days/wk. Before and after 3 wk of acclimation, the animals were given a heat-tolerance test in which rectal (Tre) and mean skin (Tsk) temperatures, heart rate, and sweat rate (msw) were monitored during a 90-min exposure to 45 degrees C heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 0 publications
1
69
0
Order By: Relevance
“…In contrast to these observations, short-term heat acclimation increases the activity of the sweat glands. In short-term heat acclimation trials, Taylor (1986) and Sato et al (1990) observed increased sweat output, an increased size of the eccrine sweat glands, and increased sensitivity of the sweat glands to methacholine stimulation. These findings indicate that short-and long-term acclimatization are mediated by different physiological mechanisms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to these observations, short-term heat acclimation increases the activity of the sweat glands. In short-term heat acclimation trials, Taylor (1986) and Sato et al (1990) observed increased sweat output, an increased size of the eccrine sweat glands, and increased sensitivity of the sweat glands to methacholine stimulation. These findings indicate that short-and long-term acclimatization are mediated by different physiological mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…However, prior heat exposure for lasting several consecutive days, improves heat resistance (Sato & Sato, 1983;Sato et al, 1990;Nielsen, 1998) by increasing sweat output, lowering the heart rate, and slowing the rise in the core temperature (Wyndham, 1967;Nadel et al, 1974;Ogawa & Sugenoya, 1993;Nielsen, 1998). Contrary to the phenomenon observed during short-term heat acclimation, when long-term heat acclimation is compared to short-term heat acclimation after exposure to equal amounts of heat, the subjects who were long-term heat acclimatized sweat less (Matsumoto et al, 1993;Ogawa & Sugenoya, 1993;.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that the controlledhyperthermia model will induce a more complete and sustained heat adaptation than either the constant or the selfregulated work rate techniques 56,57,70) . Notwithstanding differences in heat adaptation methods, one typically observes an enhancement of eccrine sweat gland (sudomotor) function 1,18,41,51,56,65) , which serves to boost our most effective means of heat dissipation within hot environments. Specifically, there is an increased steady statesweat rate (two-fold elevation), heightened sweat gland sensitivity to increments in T c , a reduced temperature threshold for sweating onset, more effective reabsorbtion of sodium and chloride within the sweat duct, and better conservation of the extracellular electrolyte content and fluid volume.…”
Section: Heat Adaptationmentioning
confidence: 99%
“…A possible explanation may lie in the physiology of the skin appendages (e.g., the sweat glands), which have been recognized as important transport pathways in iontophoresis (19 ). Interindividual differences in appendageal morphology and effects of climate on function have been reported (20,21 ) and may account for the greater variation observed in vivo as a function of ambient conditions. Additional work is clearly needed to better understand these observations.…”
Section: Comparison With In Vitro Datamentioning
confidence: 99%